2012
DOI: 10.1039/c2cp40272f
|View full text |Cite
|
Sign up to set email alerts
|

Parahydrogen induced polarization in face of keto–enol tautomerism: proof of concept with hyperpolarized ethanol

Abstract: Hyperpolarization (HP) techniques are increasingly important in magnetic resonance imaging (MRI) and spectroscopy (MRS). HP methods have the potential to overcome the fundamentally low sensitivity of magnetic resonance (MR). A breakthrough of HP-MR in life sciences and medical applications is still limited by the small number of accessible, physiologically relevant substrates. Our study presents a new approach to extend PHIP to substrates that primarily cannot be hyperpolarized due to a steady intramolecular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 39 publications
0
39
0
2
Order By: Relevance
“…Parahydrogenation of vinyl acetate (1) and hydrolysis have been previously reported 34 for obtaining hyperpolarized ethanol. Here it is shown that polarization transfer to the 13 C carboxylate signal is possible by means of magnetic field cycling.…”
Section: Discussionmentioning
confidence: 99%
“…Parahydrogenation of vinyl acetate (1) and hydrolysis have been previously reported 34 for obtaining hyperpolarized ethanol. Here it is shown that polarization transfer to the 13 C carboxylate signal is possible by means of magnetic field cycling.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the synthetic challenges, new concepts of using –OH protection in -C=C-O-R motifs have significantly expanded the reach of molecular targets for PHIP, [54, 57] because the protecting group can be removed after PHIP either metabolically [52, 54, 58] or synthetically. [57] …”
Section: Parahydrogen Induced Polarization (Phip)mentioning
confidence: 99%
“…Finally, the sidearm is cleaved off, yielding the hyperpolarized metabolite . A similar approach has been investigated for hyperpolarizing ethanol and has recently been shown to be applicable in gas‐phase reactions . Polarization transfer in PHIP‐SAH has been achieved so far by a field‐cycling procedure, in which a sample is shuttled into a magnetic field below the earth's field, followed by re‐magnetization to transfer proton polarization to 13 C‐labeled nuclei .…”
Section: Figurementioning
confidence: 99%